Mapping the inter-district disparities in primary education development in Bihar - Shreyanshi Shukla; Seema Tiwari (National Geographical Journal of India, 2023)
Universal Primary Education aims to ensure that all children achieve primary education within a stipulated timeframe. In moving towards the attainment of this goal, it is essential to ensure that disparities do not exacerbate. The primary focus of this study is to identify disparities in school access, infrastructure, and outcomes at the primary school level in Bihar. To fulfill this purpose, secondary data was collected from official sources, including Unified District Information of School Education+ (U-DISE+), Bihar Education Project Council (BEPC), Census of India (2011), the National University of Educational Planning and Administration (NUEPA), and other related publications. To measure the development of primary education, four key parameters access to schools, infrastructure, teacher availability, and school outcomes are utilized. These parameters are further broken down into fifteen sub-parameters. The raw values of each of these fifteen indicators were standardized using the Z-score method, and an Integrated Composite Index was computed. Based on the values of this composite index, districts are ranked relative to their development status. The findings reveal that Rohtas, Siwan, Gopalganj, Nawada, and Bhojpur are relatively performing well, while Samastipur, Pashchim Champaran, Madhubani, Araria, and Purab Champaran trail behind on many parameters.